2011 IEEE International Symposium on Information Theory Proceedings 2011
DOI: 10.1109/isit.2011.6034237
|View full text |Cite
|
Sign up to set email alerts
|

On the throughput of wireless interference networks with limited feedback

Abstract: Abstract-Considering a single-antenna M -user interference channel with symmetrically distributed channel gains, when the channel state information (CSI) is globally available, applying the ergodic interference alignment scheme, each transmitterreceiver pair achieves a rate proportional to 1 ⁄2 of a single user's interference-free achievable rate. This is substantially higher than the achievable rate of the conventional orthogonal transmission schemes such as TDMA. Since the rigid requirement on the CSI may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Thus, the network is interference-limited and it is preferred to more accurately perform interference alignment rather than power control. This result coincides with the trade-off observed in [6].…”
Section: Numerical Evaluationsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the network is interference-limited and it is preferred to more accurately perform interference alignment rather than power control. This result coincides with the trade-off observed in [6].…”
Section: Numerical Evaluationsupporting
confidence: 91%
“…However, the bandwidth of the feedback channels is limited in practice so that the terminals may not be able to attain sufficiently accurate CSI. It has been shown that even with limited feedback, if proper rate adaptation is performed the interference alignment scheme can still outperform TDMA, in terms of sum throughput [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, digital/analog channel state feedback schemes have been proposed in the literature to acquire CSI estimation at transmitters (see e.g. [7], [8], [9]). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it provides either the quantized version or the un-coded version of the channel gains to the other terminals through digital feedback signals or analog feedback signals, respectively. It has been shown that if the number of feedback bits of the digital feedback signals [7]- [10] or the transmission powers of the analog feedback signals [11] properly scale with transmission power, the outstanding performance of interference alignment is still achievable. Furthermore, it has been shown in reference [10] that even with a limited number of feedback bits, the throughput of applying interference alignment can still be larger than that achieved by TDMA.…”
Section: Introductionmentioning
confidence: 99%